Assessing the role of PPPs in addressing proximity and systemic challenges in regional innovation policy - Iryna Kristensen (University of Salzburg, Department of Social Sciences and Economics, 2015)
Public-Private Partnerships (PPPs) are argued to be able to add greater value to innovation processes by fortifying the quality of innovation systems by linking regional public and private actors together and exploiting a wide range of sources of innovation. The effectiveness of interface management and resource allocation as well as the dynamics of multifaceted interactions, however, will strongly depend on the degree of proximity between innovation agents. While it is difficult to determine the optimal degree of proximity for multi-sector cooperation in addressing systemic challanges, there is little doubt that certain level of cognitive, organizational, institutional, social and geographical closeness is conductive to interaction and learning. This paper applies a partnership-based approach to investigate the interrelation between dimensions of proximity and systemic failures and observes potential regional and sectoral variations with respect to proximity dimensions and their implication for regional innovation system efficiency. A matrix linking five dimensions of proximity with four categories of systemic problems serves as a basis for analysis. Six PPPs from two regions in Sweden (i.e. Sydsverige and Övre Norrland) are selected for empirical study.
Keywords: 330